Reviewing Evidence Based-Design (EBD)for healthcare to achieve best possible outcome - Mohd Nawawi, Norwina (2013)
An overview of the history and development of Evidence Based- Design as aftermath of Evidence Based Medicine into the realm of healthcare facility designs. The presentation explore latest EBD research,determine components that research had proven to support healing, discusses clinical employability through good design and update with continuous improvement of EBD to meet current needs of flexibility and adaptability. The presentation is based on literature review, current research and discussions.